Renewable Energy Investment for Middle and Upper Class Housing Sector in Indonesia: Investigating the Scope for a Change in Policy - Tony K. Hariadi; Milou Derks; Agus Jamal; Slamet Riyadi (Universitas Muhammadiyah Yogyakarta, 2018)
The household sector plays an important role in the energy demand in Indonesia. Households consume more than 50% of total energy in many major cities in Indonesia and account for 34% of the total energy demand. The main share of capital allocation and attention, however, has gone to rural electrification programs over the past years with mixed results, due to an abundance of problems during the operation phase. We propose that government attention and capital should be broadened to policy development for solar home systems for urban areas. The problems that are encountered by rural electrification projects are mainly due to a lack of resources and unclear task allocation between involved parties and difficulties of addressing problems in remote environments. These risks are insignificant in urban areas where maintenance services are available and where solar home systems can be commercially interesting for higher income consumers without the need for subsidy. By means of a cost benefit analysis, this paper shows that solar home systems can be commercially interesting for households in urban areas. Different investment scenarios were worked out with systems costing 5%, 10%, and 15% of the total average house price. The analysis indicates that the policy is feasible when solar systems are coupled to the grid but not for off-grid systems. This is because the battery leads to high investment and maintenance cost. From a government point of view, developing policy towards renewable energy usage in urban households could help to reach national electrification and environmental targets without extra capital allocation as well as relieve pressure on the already overburdened state electricity company, the PLN.